(untitled) (World Economics and Finance Bulletin, 2021)
This scientific publication examines the measures taken by the government in 1994-2007 to synchronize the functioning of the system of business entities, along with other economic mechanisms of the state and this article proves based on the official data that they were able to prevent certain negative consequences emanating from the global financial and economic crisis that broke out in 2008 on the macroeconomic and social situation in the country. It should be stressed that proper conclusions have been made on the reforms in the national economy based on the information and statistic data of official recourses of the Republic of Uzbekistan.